Application of the OpenCV Library in Indoor Hydroponic Plantations for Automatic Height Assessment of Plants - Pietrzykowski, Sławomir; Wymysłowski, Artur (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
This paper presents a method for automatic plants’ height measurements in indoor hydroponic plantations by using the OpenCV library and the Python programming language. Using the elaborated algorithm and Raspberry Pi driven system with an external camera, the growth process of multiple pak choi cabbages (Brassica rapa L. subsp. Chinensis) was observed. The main aim and novelty of the presented algorithm was to observe the plants’ height in hydroponic stations, where the reflective foil is used, to extract the plants’ growth rate as a parameter. Basing on the pictures of the hydroponic plantation, the bases of the plants, reflections, and plants themselves were separated. Finally, the algorithm was used for plants’ height estimation. The achieved results were then compared to the results obtained manually. The algorithm will be used in future research for plants’ growth optimization.